Test-retest reliability, sensibility and construct validity of the frequency speed of kick test in male black-belt taekwondo athletes - Ferreira da Silva Santos, J.; Lopes-Silva, J. P.; Loturco, I.; Franchini, E. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2020)
Aim. The purpose of the present study was to describe the reliability, sensibility and construct validity (discriminant) of male taekwondo athletes in the frequency speed of kick test (FSKT) using single and multiple sets. Material, Methods and Results. The study was divided in two parts. The first part consisted of fourteen male black-belt taekwondo athletes. Test and retest were carried out on separate occasions 1 week apart. The total number of kicks generated during FSKT10s and each set of FSKTmult, the sum of kicks during five sets, and kicks decrement did not display any difference. The ICC and SEM for absolute and relative performance during FSKT10s were 0.95 and 0.60, respectively. The ICC and SEM for absolute and relative performance during FSKTmult were between 0.63-0.83 and 0.78-3.99, respectively, for almost all measures. The limits of agreement analyses reported a mean difference between -0.1 and 0.5. The SEM was lower than SWC0.6 in almost all variables, classifying the tests as "good". This study showed that the FSKT10s and FSKTmult are reliable taekwondo-specific field tests for assessing taekwondo performance. The second part was made up of 153 male taekwondo athletes divided into National/International (n=45), Regional/ State (n=55) and non-competitor (n=53 groups. The National/International group presented superior performance compared to the non-competitors in FSKT10s and FSKTmult (FSKT3, FSKT5 and FSKTtotal) (p<0.05). Conclusions. Considering scientific criteria as an important characteristic, the results presented herein should be of interest to coaches, trainers, practitioners and taekwondo athletes, as these are the only short duration and intermittent taekwondo tests, using specific action, currently available in the scientific literature.